Analisis SWOT Kebijakan Pembelajaran Daring di Masa Pandemi Covid 19 - Ravi Udin Amirullah (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2021)
The background of this research is the Circular of the Ministry of Education and Culture of the Republic of Indonesia regarding online learning. This online learning is intended as an effort to prevent the spread of Corona Virus Disease. As we all know, with the Corona virus pandemic, not a few parties have taken policies to limit all operational activities to take part in minimizing the spread of the corona virus. This is also what the Ministry of Education and Culture has done in an effort to prevent the spread of the Corona virus. But apart from all that, the important thing to examine from the existence of this policy is related to its implementation. The policy of implementing online learning during the Covid-19 pandemic can be said to be the right policy if in its implementation it can strive to achieve learning effectiveness. Therefore, in this article, we will discuss how to implement online learning, SWOT analysis related to its implementation, and strategies that can be taken through the results of the SWOT analysis.